Improving the Skills of Memorizing Pancasila Symbols Through Picture and Picture Learning Models with Picture Media - Setiyawan, Dwi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to improve the skills of memorizing Pancasila symbols in class II students by using a picture and picture learning model with picture media. The research conducted was Classroom Action Research, which was conducted in 2 cycles. Data collection techniques were through tests, observation and documentation. The data derived from the value scores were analyzed with qualitative comparative, namely comparing the pre-cycle, cycle I and cycle II scores.The results of the study show that through the picture and picture learning model, students' memory improves, students are motivated to be more courageous in expressing opinions. With this technique can also improve students' skills in memorizing symbols. This can be seen from the average value of the skills to memorize symbols in the initial conditions of only 51.07. Then in cycle I the average value of the memorization skills of class II students increased to 68.93. In cycle II it increased to 80.00. These results indicate that the picture and picture learning model can improve the learning outcomes of Grade II students at SDN 02 Ganten.